Anthocyanins in Colorectal Cancer Prevention. A Systematic Review of the Literature in Search of Molecular Oncotargets - Medic, Nevenka; Tramer, Federica; Passamonti, Sabina (Frontiers in Pharmacology, 2019)
Background Colorectal cancer (CRC) is the malignant process that surges in the terminal part of gastrointestinal tract when adenomatous polyps convert to neoplastic cells able to infiltrate the submucosa. Despite the constant progress in applying preventive measures (screening, colonoscopy) and developing new cures (surgical and chemotherapy), CRC is still one of the leading causes of cancer death worldwide. The importance of natural dietary components in CRC prevention has been recognized. Defining the precise role of the diet and its particular molecular moieties in CRC prevention is of constant scientific interest years behind. Anthocyanins (AC), phenolic phytochemicals present in pigmented plants and vegetables, have been reported to have some role in counteracting CRC carcinogenesis. Nonetheless, evidence coming out the pre-clinical, clinical and epidemiological studies is still controversial. This review is addressing the need to better comprehend the causes of missing data and discrepancies in investigations on the role of dietary AC in modulating CRC carcinogenesis. Methods We have analyzed the scientific literature, available in PubMed database, according to PRISMA statement methodology for systematic reviews. Subsequently, two selection strategies, with their screening and eligibility criteria, were applied to retain research articles reporting in vitro and in vivo studies aimed at exploring the molecular mechanisms underlying the observed effects of AC in CRC prevention. Results From the poll of 82 identified publications, we selected 19 articles reporting experimental or observational data on the effect of AC enriched diets in CRC prevention in humans or murine species. Furthermore, we selected 10 articles reporting about molecular mechanisms of action of pure AC in CRC experimental models. Conclusions The major outcome of this review is that AC showed essentially no effect in human studies, whereas AC-enriched diets proved to be effective in experimental murine models of CRC. In cell culture tests, AC showed to interfere with cell signaling pathways related to cell growth and differentiation, apoptosis, oxygen stress and inflammation response. Further molecular characterisations are required to include AC is the panel of disease-modifying agents.